FRI0040 Helicobacter pylori infection and nsaids gastric lesions in patients with rheumatoid arthritis. (1st June 2001) - Montrone, F; Lazzaroni, M; Antivalle, M; Santandrea, S; Porro, G Bianchi; Carrabba, M
Abstract : Background: Helycobacter pylori is present in about fifty percent of patients with NSAIDs associated gastric lesions. However, studies on the interaction between H. pylori and the occurrence of NSAIDs gastrotoxicity have yielded conflicting results. Objectives: To investigate the correlation between H. pylori infection and the development of NSAIDs related gastric lesions. Methods: Data were collected during our double blind clinical and gastroscopic study on the treatment of rheumatoid arthritis with diclofenac or amtolmetinguacyl. A total of 64 patients, aged 18–80 years, suffering from rheumatoid arthritis were randomised to diclofenac (50 mg tid) or amtolmetinguacyl 600 mg bid) for 4 weeks. Clinical and endoscopic evaluation were performed at baseline and at the end of the treatment. The gastroduodenal mucosa was graded according to the Lanza scale, and H. pylori status was assessed at baseline by histology (2 biopsy samples in the antrum, one at the augulus and two in the body of the stomach) and by rapid urease test (one sample in the gastric antrum). Results: All but one of the patients reached the final visit and 59 underwent endoscopy. H. pylori infection was detected in 30 of the 59 patients (51%); this prevalence is not significantly different from the age-adjusted rate for control populations in western countries and is consistent with previous reports in rheumatoid arthritis and in arthritides of different aetiology. The gross appearance of gastroduodenal mucosa was graded as follows: grade 0, normal mucosa; grade 1, mucosal haemorrhage only; grade 2, one or two erosions; grade 3, numerous areas (3–10) of erosions; grade 4, large number of erosions (> 10) or an ulcer. Considering together patients with endoscopic grading 0–1–2 (normal or minimal lesions) and grading 3–4 (numerous erosions or ulcer), 6/30 (20%) of the H. pylori positive patients and 9/29 (31%) of the H. pylori negative patients had endoscopic scores of 3 or 4 (p < 0.05, CL -33+11%). In this trial 60% of significant gastric lesions (score 3–4) occurred in uninfected patients; this finding supports the hypothesis that most NSAIDs gastric lesions develop through mechanisms that do not require the presence of H. pylori. Our data are not in contrast with recent reports, suggesting that H. pylori not only is unimportant but may rather play a somewhat protective role. Conclusion: In this study we did not find any statistically significant correlation between H. pylori status and NSAIDs gastrolesivity. However, most gastric lesions (60%) occurred in H. pylori negative patients, suggesting that the presence of the infection is not a risk factor for the occurrence of NSAIDs related gastric lesions.